2010
DOI: 10.1007/s00432-010-0849-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes related to a synergistic effect of taxane and suberoylanilide hydroxamic acid combination treatment in gastric cancer cells

Abstract: The combination of taxane and SAHA could be efficacious for the treatment of gastric cancer. The genes that were related to the synergistic response to taxane and SAHA could serve as surrogate biomarkers to predict the therapeutic response in gastric cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…Although treatments involving combinations of docetaxel and sirtuin inhibitors have not been reported, combinations of docetaxel and other HDAC inhibitors such as trichostatin A and suberoylanilide hydroxamic acid (SAHA) have been reported to have synergistic effects related to caspase activation or tubulin acetylation in several cancer cell lines [48][50]. In our study, it remains unclear if the tubulin acetylation by tenovin-6 always affected the antitumor effect, because the tubulin acetylation was shown only in one cell line.…”
Section: Discussionmentioning
confidence: 74%
“…Although treatments involving combinations of docetaxel and sirtuin inhibitors have not been reported, combinations of docetaxel and other HDAC inhibitors such as trichostatin A and suberoylanilide hydroxamic acid (SAHA) have been reported to have synergistic effects related to caspase activation or tubulin acetylation in several cancer cell lines [48][50]. In our study, it remains unclear if the tubulin acetylation by tenovin-6 always affected the antitumor effect, because the tubulin acetylation was shown only in one cell line.…”
Section: Discussionmentioning
confidence: 74%
“…FBLN4 promoter methylation has frequently been found in lung cancers43 and melanoma cells 44. Other studies have reported that FBLN4 is overexpressed in tumors of the digestive system4547 and in gynecological tumors;4850 FBLN4 overexpression correlates with tumor progression and poor prognosis in these studies. In contrast, FBLN4 is downregulated in prostate cancer 51.…”
Section: Discussionmentioning
confidence: 50%
“…Reportedly, the combination of SAHA and XL184 synergistically induced cell apoptosis and inhibited tumor growth of prostate and lung cancer cells [19]. The similar results were observed in gastric [20] and hepatocellular [21] cancer cells, treated by oxaliplatin and SAHA. Therefore, they might be employed to treat the glioma if both hepatic and renal injuries are avoided and ameliorated in clinical practice.…”
Section: Discussionmentioning
confidence: 53%